Biosensing using an asymmetric split-ring resonator at microwave frequency. Issue 172 (12th June 2016) - He, Xunjun; Hao, Xiuli; Yan, Shitao; Wu, Fengmin; Jiang, Jiuxing
ABSTRACT: In this paper, an asymmetric split-ring resonator (aSRR) is proposed and experimentally demonstrated for a biosensing device at microwave. Compared with the transitional sensor, the proposed biosensor has a single aSRR-assisted transducer and is excited by a time varying magnetic field component of a high-impedance microstrip line to realize strong and localized field enhancement in the sensing region and achieve high quality factor ( Q -factor). The measured and simulated results show that the aSRR structure is a compact configuration, and can achieve narrow resonance with a higher Q -factor than the symmetric one. Moreover, the resulting biosensor device exhibits that the frequency shifting is observed when the sensor is loaded with different glucose concentrations, i.e., 0.25%, 1.25%, and 5%, and the corresponding shifting are 170MHz, 280MHz, and 340MHz, respectively. Therefore, the proposed biosensor offers advantages of label-free detection, a simple and direct scheme, and cost-efficient fabrication.